(untitled) (Proceedings of Southern Federal University. Philology, 2018)
Taisiya I. Skorobogatova, Tatyana A. Shkuratova (Rostov-on-Don, Russian Federation) The article views two historically interrelated phenomema, interconnection of which has continued for 900 years (since the Norman conquest of England until the end of the World War II), which are anglicization of the French language and gallicization of the English language. The aim of the article is to reveal and demonstrate the development of linguistic research, resulting in contemporary studies of anglicists and experts in the field of the French language studies, on the origin of English and French vocabulary, and also to present and compare quantitative characteristics of English loanwords in French and the number of English words ascending to French and Latin. These two typologically distant languages are united by the words of Latin origin, however, in case of the English language it’s more precise to talk about the words of Latin and French origin 85 % of vocabulary), while in case of the French language it’s about 80 % of vocabulary ascending to Latin. The authors of the article note that the history of formation and long-term coexistence of the English and French languages has no equivalents in the evolution of the world’s languages. Two powerful and beautiful languages has developed on the basis of one another, so nowadays there are no reasons to tell that one of them is more prestigious than the other and that one of them is losing its national identity. Each of the languages viewed has substantial intralinguistic resources to preserve its peculiarity: “the most ungrateful daughter of Latin”, the most Germanic of all the Romance languages and the most “Mediterranean” Germanic language. Key words: anglicization, the French language, gallicization, the English language, English loanwords, anglicisms, gallicisms, Latin. DOI 10.23683/1995-0640-2018-1-54-59